2019
DOI: 10.1186/s13054-019-2711-3
|View full text |Cite
|
Sign up to set email alerts
|

Lasting s-ketamine block of spreading depolarizations in subarachnoid hemorrhage: a retrospective cohort study

Abstract: ObjectiveSpreading depolarizations (SD) are characterized by breakdown of transmembrane ion gradients and excitotoxicity. Experimentally, N-methyl-d-aspartate receptor (NMDAR) antagonists block a majority of SDs. In many hospitals, the NMDAR antagonist s-ketamine and the GABAA agonist midazolam represent the current second-line combination treatment to sedate patients with devastating cerebral injuries. A pressing clinical question is whether this option should become first-line in sedation-requiring individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…is has been translated to clinical TBI research: in one study of 115 braininjured patients, ketamine administration (with a median dose of 200 mg) was found to reduce the occurrence of the isoelectric spreading depolarizations that are seen in traumatized human cortex [139]. In another study of 66 patients with aneurysmal subarachnoid hemorrhage, (S)-ketamine infusion (with a mean dose of 2.8 ± 1.4 mg/kg/hour) significantly decreased the incidence of spreading depolarizations [142]. While the role of ketamine in spinal cord injury has been shown in animal models [143,144], this has not yet been translated to human research.…”
Section: Neurologic Applications Of Ketaminementioning
confidence: 99%
“…is has been translated to clinical TBI research: in one study of 115 braininjured patients, ketamine administration (with a median dose of 200 mg) was found to reduce the occurrence of the isoelectric spreading depolarizations that are seen in traumatized human cortex [139]. In another study of 66 patients with aneurysmal subarachnoid hemorrhage, (S)-ketamine infusion (with a mean dose of 2.8 ± 1.4 mg/kg/hour) significantly decreased the incidence of spreading depolarizations [142]. While the role of ketamine in spinal cord injury has been shown in animal models [143,144], this has not yet been translated to human research.…”
Section: Neurologic Applications Of Ketaminementioning
confidence: 99%
“…We then excluded articles that were reviews, those that were not in English, and those that did not attempt to detect spreading depolarizations. There were 40 articles included in the initial search, with 3 additional articles from 2019 or appropriate for inclusion but missed on our initial search that were added during manuscript preparation and peer review [15][16][17]. Otherwise, the studies were published between 1971 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…One of the retrospective studies measured the frequency of SDs in patients with acute brain injury, including SAH, and found that use of ketamine was associated with fewer SDs as compared to other sedatives [58]. Another retrospective study looked specifically at ketamine in patients requiring a higher level of sedation and found that the onset of ketamine infusion was associated with a decreased incidence of subsequent SDs [15]. A third retrospective study looked at home medications prior to hospital admission, determined if they fell into SD-promoting or SD-inhibiting drug categories, and found that SD-inhibiting drugs were associated with a reduction in DCI but had no effect on measured functional outcomes; however, this study could not determine the actual incidence of SDs in their patients [59].…”
Section: Clinical Treatment Studiesmentioning
confidence: 99%
“…We read with interest the recent article by Santos et al regarding the use of S-ketamine to decrease spreading depolarizations and improve cytotoxic neuronal edema in patients with aneurysmal subarachnoid hemorrhage [1]. They note that the active enantiomer S(+) ketamine is two times stronger than the racemic form and four times stronger than the R(−) enantiomer [1]. Further, they report that the upper therapeutically recommended dose of S-ketamine for sedation is 2 mg/kg BW/h, but if deemed necessary, neuro-intensivists are using doses of up to 7 mg/kg BW/h.…”
mentioning
confidence: 99%
“…On top of this, there are numerous side effects of a wide range of medications. For our retrospective cohort study, we identified 66 patients from a prospectively collected database using prespecified criteria (32 from the University of Heidelberg, recruited 2004-2014, and 34 from Charité-Universitätsmedizin Berlin, recruited 2005-2010) [1]. Laboratory values are readily available for the Berlin patients of whom 14 were treated with S-ketamine.…”
mentioning
confidence: 99%